What is home, Mum? - Khan, Sabba (Street Noise Books, 2022)
As a second-generation Pakistani immigrant living in East London, Sabba Khan paints a vivid snapshot of contemporary British Asian life and investigates the complex shifts experienced by different generations within immigrant communities, creating an uplifting and universal story that crosses borders and decades. Race, gender, and class are explored in a compelling personal narrative creating a strong feminist message of self-reflection and empowerment which is illuminated in stunning artwork.